Kajian Terapi Akupunktur [Kombinasi Titik Lokal dan YNSA] terhadap Low Back Pain : Biokimiawi Kolesterol Darah - Wardoyo, Suwaji Handaru; Badri, Sholichan (Care : Jurnal Ilmiah Ilmu Kesehatan, 2022)
Low back pain (LBP) commonly happens and affects people in various types of work. High cholesterol level is not only a risk for plaque in the blood vessels but also a risk for LBP pain. The aim was to analyze the biochemistry of cholesterol in LBP patients receiving acupuncture therapy. The quasi-experimental design with a pretest-posttest control group design was used at Griya Sehat Dewandaru and Prima Diagnostik Main Clinical Laboratory from March to November 2020. The total sample used was 30 patients, aged 40-60 years old, and reported Visual Analog Scale (VAS) pain scale 5-7. Acupuncture therapy was performed 10 times. Data were taken directly before therapy [T0], after five times [T5], and after ten times of therapy [T10]. The blood lipid profile assessment was carried out at T0, T5, and T10 and analyzed using SPSS version 23. The normality test using the Shapiro-Wilk test showed cholesterol, HDL, LDL, and VAS were normally distributed, while triglycerides were normally distributed by the Chi-Square test. Paired T-test results on cholesterol, LDL, and VAS showed a significant difference for all groups (p=0.000). Acupuncture therapy with a combination of local points and Yamamoto New Scalp Acupuncture [YNSA] points as much as 10 times was proven to reduce cholesterol by 12.6%, LDL by 20%, and VAS by 67.67%.